Reciprocal interactions between β1-integrin and epidermal growth factor receptor in three-dimensional basement membrane breast cultures: A different perspective in epithelial biology - Wang, Fei (The National Academy of Sciences, 1998)
Anchorage and growth factor independence are cardinal features of the transformed phenotype. Although it is logical that the two pathways must be coregulated in normal tissues to maintain homeostasis, this has not been demonstrated directly. We showed previously that down-modulation of β1-integrin signaling reverted the malignant behavior of a human breast tumor cell line (T4–2) derived from phenotypically normal cells (HMT-3522) and led to growth arrest in a three-dimensional (3D) basement membrane assay in which the cells formed tissue-like acini (14). Here, we show that there is a bidirectional cross-modulation of β1-integrin and epidermal growth factor receptor (EGFR) signaling via the mitogen-activated protein kinase (MAPK) pathway. The reciprocal modulation does not occur in monolayer (2D) cultures. Antibody-mediated inhibition of either of these receptors in the tumor cells, or inhibition of MAPK kinase, induced a concomitant down-regulation of both receptors, followed by growth-arrest and restoration of normal breast tissue morphogenesis. Cross-modulation and tissue morphogenesis were associated with attenuation of EGF-induced transient MAPK activation. To specifically test EGFR and β1-integrin interdependency, EGFR was overexpressed in nonmalignant cells, leading to disruption of morphogenesis and a compensatory up-regulation of β1-integrin expression, again only in 3D. Our results indicate that when breast cells are spatially organized as a result of contact with basement membrane, the signaling pathways become coupled and bidirectional. They further explain why breast cells fail to differentiate in monolayer cultures in which these events are mostly uncoupled. Moreover, in a subset of tumor cells in which these pathways are misregulated but functional, the cells could be “normalized” by manipulating either pathway.